(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Carcinoma cervix is one of the cause of female death in developing country like Bangladesh. Prevention can be done by several screening procedure like VIA, Pap’s smear, HPV DNA testing, Colposcopy and colposcopy directed biopsy. We can markedly reduce the mortality and morbidity by these procedures and can be detected carcinoma in precancerous and very early carcinoma stage. This study was conducted to compare HPV DNA testing and pap’s smear for identification of cervical precancerous lesions in VIA positive cases. Materials and methods: It was an analytical type of cross sectional study. Data were obtained in outpatient Department of Gynecology and Obstetrics, Chattogram Medical College Hospital, Chattogram from July 2014 to December 2014. Total 90 subjects were included in the study consecutively after considering inclusion and exclusion criteria and taking written informed consent. Data analysis was done by SPSS (Version 17). Results: Histopathology findings of biopsy materials of colposcopy positive cases where 8(28.6%) were chronic cervicitis, 10(35.7%) were CIN I, 7(25.0%) were CIN II, 3(10.7%) were CIN III. Total 20(71.4%) cases were found positive or precancerous. Regarding validity analysis of different tests that were performed for cervical precancerous conditions taking histopathology results as a gold standard, sensitivity of Pap’s smear was found lower (75.0%) than the HPV DNA whereas specificity of Pap’s Smear was higher (87.5%) then the specificity of HPV DNA (75.0%). Conclusion: HPV DNA testing was both more sensitive and specific near to Pap cytology. So the use of a less invasive and more user friendly primary screening strategy like HPV-DNA testing may be required to achieve the coverage necessary for effective reduction in cervical cancer mortality. Chatt Maa Shi Hosp Med Coll J; Vol.18 (2); July 2019; Page 27-32